Food preferences and values, dietary transition, and food system transformation in Viet Nam and worldwide - Bell, Winnie. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Food and Nutrition Policy and Programs.; Advisor: William Masters.; Committee: Jennifer Coates, Jessica Fanzo, and Norbert Wilson.; Keywords: Public health, and Economics.